Imaging features of multiple myeloma extramedullary lesions in the liver with 18F-FDG PET/CT, contrast-enhanced CT and MRI - Papamichail, Dimitris; Goldschmidt, Hartmut; Dimitrakopoulou-Strauss, Antonia (Diagnostics, 2019)
Ηepatic involvement in multiple myeloma is not common; nevertheless, it is associated with poorer outcome. Heterogeneous features have been described in few published reports so far. We present the imaging findings of PET/CT in comparison to those of MRI for two multiple myeloma (MM) patients, one with a liver lesion suspicious for myeloma metastasis on PET and one with multiple liver lesions suspicious for myeloma metastases on MRΙ. The subsequent ultrasound-guided needle biopsies confirmed the extramedullary spread of the disease in both patients. The first case exhibited a match in both functional imaging modalities (PET and MRI) but a mismatch of intense metabolic activity on 18F-fluorodeoxyglucose (18F-FDG) PET/CT and iso-attenuating liver parenchyma on contrast-enhanced CT. The second case showed a mismatch of signal elevation persistence on diffusion-weighted imaging (DWI) and physiologic 18F-FDG distribution in the liver parenchyma. These cases present different imaging features in MM lesions of the liver using PET/CT and MRI, reflecting the high disease heterogeneity in patients with MM and demonstrating that the use of both PET/CT and MRI may offer complementary information.
Gesehen am 17.02.2020